Processing Window and Microstructure of NiCoCrAlY Coating Deposited on Cast Iron Using Multilayer Laser Cladding - Hao Liu; Peijian Chen; Haifeng Yang; Jingbin Hao; Xianhua Tian; Xiuli He; Gang Yu (Journal of Spectroscopy)
Cast iron is an iron-carbon alloy widely used in mechanical engineering. Nickel-base or cobalt-base alloy coatings prepared by laser cladding can improve the surface properties of cast iron, thereby increasing the service life of the components; however, due to the poor weldability and high carbon content of cast iron, the use of laser cladding to prepare alloy coatings faces many difficulties. To reduce the brittleness of the bonded interface, laser cladding was applied to the surface of cast iron using a multilayer deposition strategy. Through testing of the single-track laser cladding, the causes of defects in the coating are analysed, including poor bonding, slag inclusions, and pores. An analytical model based on mass and heat conservation is developed, and a processing window of laser tracks without defects is determined thereby. NiCoCrAlY alloy coating prepared by overlapping laser tracks mainly consists of γ-(Fe, Ni) dendrites and interdendritic M7C3 and M23C6 carbides. Although there are no cracks in a single laser track, cracks are detected when laser tracks are overlapped under the same process parameters. The increase in laser power helps to reduce cracking susceptibility on this occasion. The morphology of the grain in NiCoCrAlY alloy coating is mainly epitaxially grown columnar crystals. The increase in microhardness of the coating is mainly attributed to ductile dendrites, precipitated carbides, and grain refinement.